2020
DOI: 10.3389/fnins.2020.576813
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol Protects Neural Stem/Progenitor Cells Against Ketamine-Induced Injury Through Estrogen Receptor β Pathway

Abstract: Ketamine inhibits neural stem/progenitor cell (NSPC) proliferation and disrupts normal neurogenesis in the developing brain. 17β-Estradiol alleviates neurogenesis damage and enhances behavioral performance after ketamine administration. However, the receptor pathway of 17β-estradiol that protects NSPCs from ketamine-induced injury remains unknown. In the present study, we investigated the role of estrogen receptor α (ER-α) and estrogen receptor β (ER-β) in 17β-estradiol's protection against ketamine-exposed NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Estradiol also promotes cell proliferation and inhibits cell death in the SGZ by modulating the activity of estrogen receptors [236]. Studies have shown that treatment with exogenous estradiol inhibits the decrease in NSC neurogenesis, increase in cell death and impairment of cognition induced by exposure to ketamine by modulating the estrogen receptor β pathway associated with GSK-3β [240,241]. In addition, high exogenous and endogenous estradiol levels may increase the dendritic spine density in CA1 hippocampal pyramidal neurons, and dendritic morphology is regulated in a manner dependent on the concentration of estradiol [242,243].…”
Section: Hormone Imbalancesmentioning
confidence: 99%
“…Estradiol also promotes cell proliferation and inhibits cell death in the SGZ by modulating the activity of estrogen receptors [236]. Studies have shown that treatment with exogenous estradiol inhibits the decrease in NSC neurogenesis, increase in cell death and impairment of cognition induced by exposure to ketamine by modulating the estrogen receptor β pathway associated with GSK-3β [240,241]. In addition, high exogenous and endogenous estradiol levels may increase the dendritic spine density in CA1 hippocampal pyramidal neurons, and dendritic morphology is regulated in a manner dependent on the concentration of estradiol [242,243].…”
Section: Hormone Imbalancesmentioning
confidence: 99%
“…Several published studies show that estrogen stimulates both proliferation and differentiation of NSC/NPCs (Okada et al, 2010;Li et al, 2020) and attenuates damage to neurogenesis in the developing brain caused by chemical drug exposure (Li et al, 2019); however, another study shows that 10 nM estradiol increases NSC/NPCs proliferation and stimulates differentiation into neurons in vitro, but 50 nM estradiol markedly decreases NSC/NPCs proliferation (Zhang et al, 2019a). Thus, the effects of maternal estradiol on neurogenesis of fetal hypothalamic NSC/NPCs may be dose dependent, and the dose that caused metabolic disorder in our mouse model exerted a different effect on proliferation and differentiation.…”
Section: High Maternal Estradiol Is Usually Induced By Ovarian Stimulationmentioning
confidence: 99%
“…However, increasing evidence suggests we need to increase the therapeutic efficacy of the transplanted cells to enhance stroke recovery (Hermann et al, 2014;Damian et al, 2021). These improvements may be achieved by manipulating17β-estradiol (Liang et al, 2016;Li et al, 2020;Mihai et al, 2021). 17β-estradiol has beneficial effects on various stem cells and progenitor cells in improving recovery after myocardial ischemia (Yuan et al, 2018) and cerebral ischemia (Liang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%